DETECTION OF SALMONELLA TYPHIMURIUM BACTERIA ON BAKERY PRODUCTS SAMPLES USING BOILING ISOLATION TECHNIQUE - Alfi Sophian; Ratna Purwaningsih; Muhammad Tri Sutrisno; Purwadi Purwadi; Arif Wahyudi (Universitas Muhammadiyah Magelang, 2022)
Detection of Salmonella typhimurium ATCC 14028 bacteria in bakery product samples by real-time PCR using boiling isolation technique. The basis of this research is to have an impact on economic value in carrying out the confirmation test for Salmonella typhimurium ATCC 14028, where testing is carried out conventionally will require large costs, so it is necessary to innovate in terms of modifying the testing phase so that it is more effective and efficient. The purpose of this study was to see whether the boiling isolation technique could be used for the detection test for Salmonella typhimurium ATCC 14028 on bacterial product samples. The sample in this study consisted of 15 types of bacterial product samples spiked with Salmonella typhimurium ATCC 14028 cultures that had been cultured into phase 2 working cultures. The method used in this study was qPCR analysis using the SYBR Green method. The results of real-time PCR analysis obtained Ct values in the range 7.55 - 8.91 with an average of 8.28 and a Tm value in the range 85.50 - 86.20 with an average of 85.77 Based on these data it can be concluded that the detection of Salmonella typhimurium bacteria ATCC 14028 with real-time PCR using boiling isolation technique can be applied for testing on bakery product samples.